Vaccine confidence among parents: Large scale study in eighteen European countries. Issue 6 (5th February 2020) - Hadjipanayis, Adamos; van Esso, Diego; del Torso, Stefano; Dornbusch, Hans Jürgen; Michailidou, Kyriaki; Minicuci, Nadia; Pancheva, Ruzha; Mujkic, Aida; Geitmann, Karin; Syridou, Garyfallia; Altorjai, Peter; Pasinato, Angela; et al.
Abstract: Background: Despite the fact that vaccines save 2–3 million lives worldwide every year, a percentage of children are not getting appropriately vaccinated, thus leading to disease outbreaks. One of the major reasons of low vaccine uptake in Europe is vaccine hesitancy, contributing to the recent measles outbreaks. Monitoring of vaccine hesitancy is valuable in early identification of vaccine concerns. Methods: We performed an eighteen country European survey on parents' attitudes and behaviors regarding their children's immunization. Parents having at least one child 1–4 years old were mostly recruited by primary care paediatricians to reply to a web-based questionnaire. The questionnaire was developed by the European Academy of Paediatrics Research in Ambulatory Setting Network steering committee, based on similar surveys. An individual level hesitancy score was constructed using the answers to 21 questions, and correlations of the score with socio-demographic characteristics and types of providers were explored. To assess inter country differences, a country level self -reported confidence was defined. Results: Fifty six percent and 24% of 5736 respondents defined themselves as "not at all hesitant", and "somewhat hesitant", respectively. Parents who consulted general practitioners were more hesitant than parents who consulted pediatricians (p < 0.05). Consultation with homeopathists was associated with the highest reported hesitancy (p < 0.05). Vaccine confidence was highest in Portugal and Cyprus, and lowest in Bulgaria and Poland. Conclusion: The majority of parents in Europe believe in the importance of childhood vaccination. However, significant lack of confidence was found in certain European countries, highlighting the need for continuous monitoring, awareness and response plans. The possible influence of different types of healthcare providers on parental decisions demonstrated for the first time in our survey, calls for further research. Monitoring and continuous medical education efforts aimed mostly at those professionals who might not be likely to recommend vaccination are suggested.